DspA/E Contributes to Apoplastic Accumulation of ROS in Non-host A. thaliana - Launay, Alban; Patrit, Oriane; Wénès, Estelle; Fagard, Mathilde (Frontiers in Plant Science, 2016)
The bacterium Erwinia amylovora is responsible for the fire blight disease of Maleae, which provokes necrotic symptoms on aerial parts. The pathogenicity of this bacterium in hosts relies on its type three-secretion system (T3SS), a molecular syringe that allows the bacterium to inject effectors into the plant cell. E. amylovora-triggered disease in host plants is associated with the T3SS-dependent production of reactive oxygen species (ROS), although ROS are generally associated with resistance in other pathosystems. We showed previously that E. amylovora can multiply transiently in the non-host plant Arabidopsis thaliana and that a T3SS-dependent production of intracellular ROS occurs during this interaction. In the present work we characterize the localization and source of hydrogen peroxide accumulation following E. amylovora infection. Transmission electron microscope (TEM) analysis of infected tissues showed that hydrogen peroxide accumulation occurs in the cytosol, plastids, peroxisomes, and mitochondria as well as in the apoplast. Furthermore, TEM analysis showed that an E. amylovora dspA/E-deficient strain does not induce hydrogen peroxide accumulation in the apoplast. Consistently, a transgenic line expressing DspA/E accumulated ROS in the apoplast. The NADPH oxidase-deficient rbohD mutant showed a very strong reduction in hydrogen peroxide accumulation in response to E. amylovora inoculation. However, we did not find an increase in bacterial titers of E. amylovora in the rbohD mutant and the rbohD mutation did not suppress the toxicity of DspA/E when introgressed into a DspA/E-expressing transgenic line. Co-inoculation of E. amylovora with cycloheximide (CHX), which we found previously to suppress callose deposition and allow strong multiplication of E. amylovora in A. thaliana leaves, led to a strong reduction of apoplastic ROS accumulation but did not affect intracellular ROS. Our data strongly suggest that apoplastic ROS accumulation is one layer of the non-host defense response triggered by the type three effector (T3E) DspA/E, together with callose deposition.